Efecto de extractos vegetales y bacterias halófilas en el control de Meloidogyne incognita en condiciones de laboratorio - Urrutia Quispe, Lucia Elizabeth (2019)
The purpose of this research was to determine in laboratory conditions the effect of three doses of plant extracts and halophilic bacteria on the emergence of juveniles of the second stage (J2) of Meloidogyne incognita. The treatments under study were T1 (control, only Meloidogyne incognita), T2 (60 l / ha of vegetable extract and halophilic bacteria plus Meloidogyne incognita), T3 (80 l / ha of vegetable extract and halophilic bacteria plus Meloidogyne incognita, T4 (100 l / ha of extract of vegetables and halophilic bacteria plus Meloidogyne incognita.) The treatments were distributed in a completely randomized design, with four treatments and six repetitions, the experimental unit was constituted by a Petri dish in which 50 eggs of Meloidogyne incognita in the state of juvenile first stage (J1), plus the doses according to the treatments The variable evaluated was the emergency percentage of J2 of Meloidogyne incognita. The data of the evaluations were submitted to the analysis of variance and to the Tukey test at 0.05%. With the application of the T2 , 6.5% emergency was obtained and with the T3 and T4 the 6% emergency of J2 compared to the 51% obtained in control treatment. All evaluated doses of plant extracts and halophilic bacteria inhibited the emergence of juveniles of M. incognita.